СТВОРЕННЯ КОНЦЕПЦІЇ ТЕРМОГРАФІЧНОЇ КЛАСИФІКАЦІЇ ВОГНЕПАЛЬНИХ ПОРАНЕНЬ М’ЯКИХ ТКАНИН (World Science, 2020)
The aim. To study the effectiveness of using dynamic digital thermography in wounded with gunshot injuries of soft tissues in a multimodal reconstruction scheme. Based on the materials received, propose the concept of thermographic classification of gunshot wounds of soft tissues. Conclusions. The use of a multimodal approach in the reconstructive treatment of gunshot wounds of soft tissues is an effective method of repairing a damaged anatomical structure. The integration of the information obtained during the DDT is the main basis for the materialization of the conceptual creation of thermographic classification of gunshot wounds of soft tissues.